2014
DOI: 10.1371/journal.pone.0104951
|View full text |Cite
|
Sign up to set email alerts
|

Altered Distribution of Peripheral Blood Memory B Cells in Humans Chronically Infected with Trypanosoma cruzi

Abstract: Numerous abnormalities of the peripheral blood T cell compartment have been reported in human chronic Trypanosoma cruzi infection and related to prolonged antigenic stimulation by persisting parasites. Herein, we measured circulating lymphocytes of various phenotypes based on the differential expression of CD19, CD4, CD27, CD10, IgD, IgM, IgG and CD138 in a total of 48 T. cruzi-infected individuals and 24 healthy controls. Infected individuals had decreased frequencies of CD19+CD27+ cells, which positively cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 59 publications
1
9
0
1
Order By: Relevance
“…However, only levels of IgG2 and IgG4 were reduced in patients with SD, with comparable levels of total IgG and IgM in patients to those of HC. Similar to our results, Esteban found that T. cruzi-infected individuals had significantly lower frequencies of SM B cells with no change in the level of total IgG (41). We speculated that decreased USM B cells may be responsible for decreased IgG2 and/or IgG4 production which need further verification.…”
Section: Discussionsupporting
confidence: 89%
“…However, only levels of IgG2 and IgG4 were reduced in patients with SD, with comparable levels of total IgG and IgM in patients to those of HC. Similar to our results, Esteban found that T. cruzi-infected individuals had significantly lower frequencies of SM B cells with no change in the level of total IgG (41). We speculated that decreased USM B cells may be responsible for decreased IgG2 and/or IgG4 production which need further verification.…”
Section: Discussionsupporting
confidence: 89%
“…Role(s) of regulatory surface receptors in the function(s) of these naïve-like B cells are not well established. CD19 + , CD27 − , IgM + , IgD + B cells increase in frequency within whole blood during clinical Chagas’ disease (13) and P. falciparum cerebral malaria (14), suggesting a causal link between IgM + /IgD + naïve-like B cells and persistence of intracellular protozoal infection. Despite these correlative findings, very little is known regarding the specific role of IgD + IL-10 producing B cells in natural infection settings, or regulatory function(s) of IgD hi expressing cells.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we were unable to obtain data on the cytokine profile and functionality of cTfh cells that could lead to a better understanding of their role in the pathogenesis of chronic Chagas heart disease. However, our detailed phenotypic characterization provides indirect evidence of a potential role of Tfh cells in the abnormal immune responses against T. cruzi (Fernández et al, 2014), establishing the basis to perform further studies to assess these processes.…”
Section: Discussionmentioning
confidence: 92%
“…Dysregulation of the cTfh cell compartment has been reported in autoimmune diseases, cancer and infections associated with abnormal B cell responses (Boswell et al, 2014;Ueno et al, 2015). However, whether Tfh cells contribute to the generation of the abnormal B cell responses observed during T. cruzi infection remains to be elucidated (Minoprio et al, 1988;Fernández et al, 2014). The aim of this work was to provide an insight in the adaptive immune response elicited by T. cruzi in humans.…”
Section: Introductionmentioning
confidence: 99%